Inheritance of Some Characters in Cucumber, Cucumis Sativus L.: I. Powdery mildew resistance and mottling of immature fruit. - IMAM, MOSTAFA K.; ABOBAKR, M. A.; YOCOUB, H. M. (The Libyan Journal of Agriculture, 2023)
The mode of inheritance of powdery mildew resistance and mottling of immature fruit was studied in four inbred lines of the cultivars Baladi, Cool Green, Poinsett and Yomaki. The local cultivar Baladi and the American cultivar Cool Green were susceptible to powdery mildew and their fruits showed no mottling during the immature stage. The American cultivar Poinsett and the Japanese cultivar Yomaki were resistant to powdery mildew and had mottled fruits in the immature stage. Genetic segregations from nine different crosses between susceptible and resistant parents indicated that resistance to powdery mildew is governed by two pairs of duplicate genes with susceptibility being dominant over resistance. This was true whether Poinsett cultivar or Yomaki was used as the resistant parent. In a cross between the two resistant cultivars Yomaki and Poinsett, the F(, F2 and backcross progenies were resistant with very few exceptions of slightly susceptible plants. Apparently the two resistant parents had the same genes for resistance. A possibility exists for the presence of some modifier genes. Segregations from the nine crosses between parents with mottled and non-mottled immature fruits indicated that mottling was dominant over non-mottling and that this character was governed by one pair of genes.